PALAEOENVIRONMENTAL EVOLUTION OF THE PLIO-PLEISTOCENE MONTE MARIO SUCCESSION (ROME, ITALY) INFERRED FROM OSTRACOD ASSEMBLAGES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
The whole "classical" Monte Mario succession has been recovered through the excavation of the Giovanni XXIII tunnel inside the city of Rome (Italy). The succession has been sampled from the Zanclean Monte Vaticano Fm. to the Lower Pleistocene Monte Mario Fm. Well-preserved and diversified ostracod faunas have been recovered and the ostracod assemblages have been studied using community structure analyses and statistical multivariate analyses. The Monte Vaticano Fm. has been referred to a bathyal marine environment (300-350 m of depth), the most represented genera being Krithe, Parakrithe, Bairdoppilata and Cytherella. The Monte Mario Fm. provided ostracod assemblages referable to littoral environments with Cimbaurila, Aurila, Costa, Carinocythereis, Leptocythere and Loxoconcha as dominant taxa. Within the Monte Mario Fm., three marine shallowing-up sequences have been recognised, the last two recording marginal marine conditions with shallow depths and variable salinity (dominant Cyprideis torosa). Two cold-water episodes have been recognised within the basal Monte Mario Fm. characterised by the occurrence of Arctica islandica and, within the upper level, by the presence of the northern guests Cytheropteron depressum, Bythocythere zetlandica, Paradoxostoma ensiforme and Paradoxostoma abbreviatum.
Keywords: Marine ostracods; Plio-Pleistocene; Central Italy; Palaeoenvironmental evolution; Community structure analysis; Multivariate statistical analysis